Introduction to Political Science Research Methods - Franco, Josh; Lee, Charlotte; Vue, Kau (Open textbook library., 2023)
Welcome to the official website for Introduction to Political Science Research Methods and Polimetrics: A Stata Companion to Introduction to Political Science Research Methods workbook! Introduction to Political Science Research Methods, authored by Dr. Josh Franco, Dr. Charlotte Lee, Kau Vue, Dr. Dino Bozonelos, Dr. Masahiro Omae, and Dr. Steven Cauchon, is an Open Education Resource textbook licensed CC BY-NC that surveys the research methods employed in political science. The textbook includes chapters that cover: history and development of the empirical study of politics; the scientific method; theories, hypotheses, variables, and units; conceptualization, operationalization and measurement of political concepts; elements of research design including the logic of sampling; qualitative and quantitative research methods and means of analysis; and research ethics. Polimetrics: A Stata Companion, authored by Dr. Josh Franco, is an Open Education Resource workbook licensed CC BY-NC and designed as a Stata companion to Introduction to Political Science Research Methods. This workbook provides a tour of the Stata software, an introduction to cross-sectional, time series, and panel data, and an introduction to a variety of models. I review models where the outcome is linear, binary, ordinal, categorical, and count. Additionally, I have an interpretation chapter on survival models.